FENOMENA FLYPAPER EFFECT PADA DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH PEMERINTAH KABUPATEN/KOTA DI SUMATERA SELATAN - Bainil Yulina Kartika Rachma Sari Rita Martini (JURNAL RISET TERAPAN AKUNTANSI, 2017)
The purpose of this study was to determine whether the DBH, DAU, DAK and PAD significantly influence the local government expenditures both partially and simultaneously and also to know whether there has been a flypaper effect on the districts / cities in South Sumatera in 2012 to 2016. The object of this research focuses on 15 districts /cities in South Sumatera province. The analytical method used in this study is multiple regression with the data panel. The results of this study stated that partially DBH, DAU, DAK and PAD have positive and significant influence to regional expenditure in South Sumatera in the year 2007-2012. Simultaneously DBH, DAU, DAK and PAD also significantly affect regional expenditure because the value F statistic is greater than the value of F tableα = 5% in the amount of 442,2431 >3,48. In the study also obtained results that occur flypaper where the largest revenue source of DAU which affect the amount of spending in the next year.